Edukasi dan Sosialisasi Gerakan masyarakat Cerdas Menggunakan Obat (Gema Cermat) - Nining Nining; Yeni Yeni (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Health problems are so complex today. It encourages the people to look for effective treatment alternatives and also efficient in terms of cost. Self medication is being an alternative that has been taken by the the people. Irrational self medication management could lead to disadvantages such as medication errors due to misdiagnosis, inappropriate drugs use due to bias of information from drug advertisements and unwanted drug reactions. Education and Socialization of  Gema Cermat was conducted by UHAMKA pharmacist lecturers on December 24th, 2017 in cooperation with PCPM Setu and pharmacists PC IAI Bekasi district as an effort in order to improve the concern, awareness, understanding and skill of people in using drugs properly and correctly. The methods used are CBIA, giving the brochure of Gema Cermat, the pocket books of drugs use and drugs classification, pre-test, post-test and materials about Gema Cermat through oral presentation by a pharmacist. The results of education and socialization of Gema Cermat are improving the values of the community regarding the proper and correct use of drugs. It could be seen from the increasing of average pre-test score, 72.5 to 89.7 on post-test. People could analyze and record data that they need to be considered on the drugs use so that  the proper and correct use of drugs can be achieved.